2014
DOI: 10.1039/c4cc06160h
|View full text |Cite
|
Sign up to set email alerts
|

Organic dyes with intense light absorption especially suitable for application in thin-layer dye-sensitized solar cells

Abstract: Three new thiazolo[5,4-d]thiazole-based organic dyes have been designed and synthesized for employment as DSSC sensitizers. Alternation of the electron poor thiazolothiazole unit with two propylenedioxythiophene (ProDOT) groups ensured very intense light absorption in the visible region (ε up to 9.41 × 10(4) M(-1) cm(-1) in THF solution). The dyes were particularly suitable for application in transparent and opaque thin-layer DSSCs (TiO2 thickness: 5.5-6.5 μm, efficiencies up to 7.71%), thus being good candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 33 publications
5
47
0
Order By: Relevance
“…It was proposed that the remarkable performances displayed by dye TTZ5 were due to good alignment of its frontier orbitals with the energy levels of the semiconductor and the redox couple, excellent light-harvesting ability, and efficient regeneration facilitated by the sulfur-containing donor group. [121] Importantly, very similar results were obtained for strip DSSCs with a larger active area of 3.6 cm 2 , for which a maximum PCE of 6.35 % was recorded, once again with TTZ5 as the sensitizer. The stability of such strip cells, constructed with dyes TTZ3-5, was also tested through monitoring of their photovoltaic parameters over a period of 1000 h, during which they were stored at 85°C in the dark: all devices showed excellent stability, and their power conversion efficiencies stayed basically constant during the entire period of time.…”
Section: Use Of Tztz-based Compounds In Dsscssupporting
confidence: 73%
See 2 more Smart Citations
“…It was proposed that the remarkable performances displayed by dye TTZ5 were due to good alignment of its frontier orbitals with the energy levels of the semiconductor and the redox couple, excellent light-harvesting ability, and efficient regeneration facilitated by the sulfur-containing donor group. [121] Importantly, very similar results were obtained for strip DSSCs with a larger active area of 3.6 cm 2 , for which a maximum PCE of 6.35 % was recorded, once again with TTZ5 as the sensitizer. The stability of such strip cells, constructed with dyes TTZ3-5, was also tested through monitoring of their photovoltaic parameters over a period of 1000 h, during which they were stored at 85°C in the dark: all devices showed excellent stability, and their power conversion efficiencies stayed basically constant during the entire period of time.…”
Section: Use Of Tztz-based Compounds In Dsscssupporting
confidence: 73%
“…[92] In the same period, several unsymmetrical D-π-A compounds, each featuring a thiazolothiazole moiety in the conjugated bridge, were reported to act as photosenzitizers in dye-sensitized solar cells, and a maximum efficiency of 7.71 %, [121] coupled with satisfactory stability of over 1000 h, [122] was observed in the presence of electron-rich propylenedioxythiophene (ProDOT) substituents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[13][14][15][16] Several studies have indicated that dye desorption from the TiO 2 surface is one of the primary reasons of performance degradation. Compared to metal-complexes, metal-free organic dyes often achieve higher molar extinction coefficients, 32,33 which are particularly important to fully absorb light in devices with short optical path lengths, for example in solid-state DSSCs (ss-DSSCs) 34 where a number of factors limit thickness of the absorbing layer to less than 3 µm. Among several alternatives to carboxylic acids, [17][18][19][20] phosphonic acids have been proposed as TiO 2 anchoring group to improve device stability.…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole group is a typical electron-withdrawing group and expected to improve the electron injection ability in DSSC working mechanism. Although imidazolic/thiazole-based organic dyes are extensively employed as DSSC sensitizers [15,16], there is a limited number of benzimidazole type sensitizer used in DSSC devices. Jia et al reported that benzimidazole group attached to the triphenylamine core increased the molar extinction coefficient and l max value of the sensitizer [17].…”
Section: Introductionmentioning
confidence: 99%